Elevations in growth hormone and glucagon-like peptide-2 levels on admission are associated with increased mortality in trauma patients. Issue 1 (December 2016) - Rowan, Matthew; Beckman, Darrick; Rizzo, Julie; Isbell, Claire; White, Christopher; Cohn, Stephen; Chung, Kevin
Abstract Background Burn and trauma patients present a clinical challenge due to metabolic derangements and hypermetabolism that result in a prolonged catabolic state with impaired healing and secondary complications, including ventilator dependence. Previous work has shown that circulating levels of growth hormone (GH) are predictive of mortality in critically ill adults, but few studies have examined the prognostic potential of GH levels in adult trauma patients. Methods To investigate the utility of GH and other endocrine responses in the prediction of outcomes, we conducted a prospective, observational study of adult burn and trauma patients. We evaluated the serum concentration of GH, insulin-like growth factor 1 (IGF-1), IGF binding protein 3 (IGFBP-3), and glucagon-like peptide-2 (GLP-2) weekly for up to 6 weeks in 36 adult burn and trauma patients admitted between 2010 and 2013. Results Non-survivors had significantly higher levels of GH and GLP-2 on admission than survivors. Discussion This study demonstrates that GH has potential as a predictor of mortality in critically ill trauma and burn patients. Future studies will focus on not only the role of GH, but also GLP-2, which was shown to correlate with mortality in this study with a goal of offering early, targeted therapeutic interventions aimed at decreasing mortality in the critically injured. Conclusions GH and GLP-2 may have clinical utility for outcome prediction in adult trauma patients.